Language outcomes of children with cerebral palsy aged 5 years and 6 years: a population‐based study. (14th November 2015) - Mei, Cristina; Reilly, Sheena; Reddihough, Dinah; Mensah, Fiona; Pennington, Lindsay; Morgan, Angela
Abstract : Aim: To examine the frequency, range, and features of language impairment in a community sample of children with cerebral palsy (CP) aged 5 to 6 years. Method: Children with CP born between 2005 and 2007 were identified through the Victorian Cerebral Palsy Register. Eighty‐four participants were recruited, representing 48% of the contacted families. The recruited sample was representative of non‐participants. Participants completed standardized measures of receptive and expressive language, and non‐verbal cognition. Results: Language impairment was identified in 61% (51/84) of participants. Twenty‐four per cent (20/84) were non‐verbal. Co‐occurring receptive and expressive language impairment was common (37/84, 44%). Isolated receptive (6/84, 7%) and expressive (4/84, 5%) impairments occurred relatively infrequently. At a group level, verbal and non‐verbal participants demonstrated deficits across language subdomains (i.e. semantics, syntax, morphology), rather than in single domains. Cognitive impairment and Gross Motor Function Classification System levels IV and V were associated with higher rates of language impairment (odds ratio [OR] 15.2, 95% confidence interval [CI] 3.2–71.8 and OR 8.5, 95% CI 1.8–40.3 respectively). Only cognition was independently associated with language impairment when both of these factors were considered within a multivariable model. Interpretation: Language impairment was common in 5‐year‐old and 6‐year‐old children with CP, affecting three out of five children. Participants were impaired across linguistic subdomains indicating a generalized language deficit. Findings suggest most children would benefit from a clinical language assessment. To target services effectively, subgroups of individuals with CP at greatest risk for language impairment need to be identified. What this paper adds: Language impairment was common in a community cohort of children with cerebral palsy aged 5 years and 6 years. Receptive and expressive language impairments were often comorbid; isolated impairments were rare. Impairments within specific subdomains of language were not apparent, indicating a generalized language deficit. Cognition was associated with language functioning. This article is commented on by Geytenbeek on pages535–536 of this issue.